The Influence of Religious and Ethical Values on Mitigating Money Politics Among Women in Aceh - Dewi, Ernita (Program Studi Aqidah dan Filsafat Islam, 2024)
Money politics continues to pose a significant challenge in Aceh, notably among populations less acquainted with political processes and facing urgent economic needs. This study aims to explore the influence of religious and ethical values in countering money politics among Acehnese women. Employing a qualitative phenomenological approach, this research gathers primary data through interviews and supplements it with secondary data from existing literature. The findings reveal that although financial and material incentives are compelling, they do not invariably secure women's votes. Adherence to religious teachings, ethical considerations, and personal life philosophies significantly influence their decision-making processes. Although women in Aceh are highly susceptible to money politics, they are more likely to decline such offers compared to men, primarily due to their strong religious and moral convictions. To combat money politics effectively, strategies should emphasize political education and economic empowerment, reinforced by robust religious and ethical instruction, aiming to cultivate a more equitable and healthier democratic environment in Aceh.